New Masters, New Servants: Migration, Development, and Women Workers in China - Mcquaide, Shiling (Labour / Le Travail, 2009)
The article reviews the book, "New Masters, New Servants: Migration, Development, and Women Workers in China," by Yan Hairong.
Keywords: BOOKS – Reviews; CHINA – Social conditions – 1976-2000; NEW Masters; New Servants: Migration; Development & Women Workers in China (Book); Nonfiction; YAN Hairong